Loss of CD24 expression promotes ductal branching in the murine mammary gland - Cremers, Natascha; Deugnier, Marie-Ange; Sleeman, Jonathan P. (Cellular and molecular life sciences, 2010)
CD24 is expressed on mammary stem cells and is used as a marker for their isolation, yet its function in the mammary gland still needs to be examined. Here we show that CD24 is expressed throughout the luminal epithelial cell layer, but only weakly in myoepithelial cells. During lactation, CD24 expression was suppressed within alveoli, but upregulated post-lactation, returning to a pre-pregnant spatial distribution. CD24-deficient mice exhibited an accelerated mammary gland ductal extension during puberty and an enhanced branching morphogenesis, resulting in increased furcation in the ductal structure. CD24-/- mammary epithelial cells were able to completely repopulate cleared mammary fat pads and to give rise to fully functional mammary glands. Together, these data suggest that while CD24 is expressed in mammary epithelium compartments thought to contain stem cells, CD24 is not a major regulator of mammary stem/progenitor cell function, but rather plays a role in governing branching morphogenesis.